Concepts of Roman law in modern justice - Nesterenko, Anna (Global Prosperity, 2022)
The article examines the main principles of Roman law adapted to the modern system of justice, which makes it possible to understand and form separate knowledge about the formation and prospects of the development of the modern system of justice, as the main component of the legal state. Separate works of contemporary legal philosophers, normative provisions of the legal monuments of the Roman state are analyzed, in which the origins of the formation of justice can be seen. Peculiarities of the fundamental principles of Roman law are studied, its constituent parts are studied, which, as a whole, formed the legal concepts of modern justice.